Developing muscle power for combat sports athletes - Jonatas Ferreira da Silva Santos (Universidad de León, 2021)
In combat sports, the specificity of the training requires that the athlete improve all performance indicators associated with the match. For this reason, muscle power seems to be determinant during the application of the techniques that result in scores, specifically punches, kicks, elbows, knees, throwing techniques, transitions to the groundwork and some groundwork techniques and sometimes, the win match by knockout. Based in these information’s, the present chapter will approach items referring to the muscle power manifestation and monitoring, and to the training prescription of exercises for the grappling, striking and mixed combat sports.